A review of the tolerability and safety of levocabastine eye drops and nasal spray. Implications for patient management - Howarth, Peter H. (Hindawi Publishing Corporation, 1995)
Levocabastine is a highly potent and selective H(1)-receptor antagonist specifically developed for topical administration by ocular and nasal routes. The clinical effects of levocabastine occur rapidly and are predominantly due to local antihistaminic effects at the site of application. Clinically, levocabastine is well tolerated with an adverse effect profile comparable with that of sodium cromoglycate and placebo. As might be expected from the route of drug administration, local irritation is the most frequent adverse event seen with levocabastine eye drops and nasal spray with an incidence comparable with that in placebo-treated controls. Intranasal application of levocabastine has been shown to have no adverse effect on ciliary activity both in vitro and in vivo, while ocular administration has not been shown to have any significant or consistent adverse effect in both animal and human studies. At therapeutic doses, levocabastine appears to be devoid of significant systemic activity producing no apparent effects on cardiovascular, psychomotor and cognitive function. Since levocabastine undergoes little hepatic metabolism, and only low plasma levels of the drug are attained following topical administration, drug interactions are unlikely.